Дослідження впливу розрідження на процес нагріву багатокамерної печі випалювання димовими газами - Жученко, О.А.; Коротинський, А.П. (Science-based technologies, 2018)
Changing the parameters of the technological mode of the process of baking carbon products allows to achieve a qualitative thermal mode, which fully determines the quality of products. Investigation of the temperature field of the furnace which depend on the technological parameters, and their rational use allows to achieve a lower output of defective products. Therefore, it is important to model these processes taking into account the maximum number of factors that will minimize the time and cost of finished products. The investigation of the influence of underpressure on the temperature fields of the furnace chamber and the process of heating the flue gases in general have been carried out. The regularities of the change in the mean value of the temperature drop across the blanks under different operating conditions were revealed. The main attention of the research was paid to the issues of homogeneity of the temperature field of blanks, which significantly affects their quality.